Systematization of nursing assistance for people with intestinal stomas: integrative review (Estima – Brazilian Journal of Enterostomal Therapy, 2018)
Objectives: to identify the national and international scientific production related to the nursing systematization with a special focus on nursing diagnoses in clients submitted to intestinal stomas; to analyze the articles collected about the theme with a view to the discussion of the contributions to specialized care in nursing in Stomatherapy. Method: integrative literature review from the descriptors: systematization of assistance, stoma and nursing diagnoses and colostomy. The search was done in the databases LILACS, SciELO and BDENF, in articles published from 2000 to 2015. Results: the integrative review showed the main nursing diagnoses to clients with intestinal stomas and confirmed the systematization of nursing assistance as an important instrument to supervise in Stomatherapy. Conclusion: the use of systematization of assistance contributes to the nurses’ clinical practice and language standardization, as it appears in the publications. The scarcity of studies published in this area evidenced the necessity to research further on the subject.